From suffering to indifference: Reaction of novice nurses to ethical challenges in first year of clinical practice - Vahid Naseri-Salahshour; Mahbobeh Sajadi (Wolters Kluwer Medknow Publications, 2019)
Background: The first year of clinical practice is one of the most important steps in nursing career life. Although, studies have been conducted on ethical issues in nurses, however, few studies have been conducted on the responses of novice nurses to ethical issues. The purpose of this study was to explore the responses of novice nurses to ethical challenges in the first year of clinical practice. Materials and Methods: This study is a qualitative study with content analysis approach was conducted with financial support of Arak University of Medical Sciences. In this study, about 11 novice nurses selected using purposive sampling from educational hospitals affiliated to Arak University of Medical Sciences. Data were collected by semi-structured interviews. The duration of the interviews was 30-110 minutes. In order to analyze the data, inductive content analysis was used. Results: Data analysis revealed two important, and different responses over time in novice nurses. So that at the beginning of practice, the reaction to ethical challenges was "suffering" and after a few months it became "indifference". Conclusions: This study showed that the response of novice nurses to ethical challenges in the first year of clinical practice was a transition from suffering to indifference. These findings can be used in nursing education, research and practice. Further research is recommended in this regard.